2020
DOI: 10.12659/msm.920482
|View full text |Cite
|
Sign up to set email alerts
|

Small Nucleolar RNA Host Gene 1 (SNHG1) and Chromosome 2 Open Reading Frame 48 (C2orf48) as Potential Prognostic Signatures for Liver Cancer by Constructing Regulatory Networks

Abstract: Background: Liver cancer is a common malignant tumor with poor prognosis. The present study sought to identify potential signatures that can predict the prognosis of patients with liver cancer. Material/Methods: The RNA sequencing (RNA-seq) and clinical information of liver cancer patients were obtained from the Cancer Genome Atlas (TCGA) database. Differentially expressed long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and messenger RNAs (mRNAs) were identified between liver cancer and adjacent normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…( 4) e cutoff value of lncRNA expression level was described. (5) Every study performed the association between expression of lncRNA and OS, and the hazard ratio (HR) value and its corresponding 95% confidence interval (95% CI) for OS was either obtained directly from actual study or indirectly it will be calculated by Engauge Digitizer 4.1 software from survival curve. (6) e hazard ratio (HR) value and its corresponding 95% confidence interval (95% CI) for the OS, RFS, and DFS were either directly acquired from the original text or will be indirectly estimated by Engauge Digitizer 4.1 software from the survival curve [13]; (4) risk of bias assessed the key factors.…”
Section: Inclusion and Exclusion Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…( 4) e cutoff value of lncRNA expression level was described. (5) Every study performed the association between expression of lncRNA and OS, and the hazard ratio (HR) value and its corresponding 95% confidence interval (95% CI) for OS was either obtained directly from actual study or indirectly it will be calculated by Engauge Digitizer 4.1 software from survival curve. (6) e hazard ratio (HR) value and its corresponding 95% confidence interval (95% CI) for the OS, RFS, and DFS were either directly acquired from the original text or will be indirectly estimated by Engauge Digitizer 4.1 software from the survival curve [13]; (4) risk of bias assessed the key factors.…”
Section: Inclusion and Exclusion Standardmentioning
confidence: 99%
“…lncRNA is a kind of endogenic RNA 200 or more nucleotides long, which is extensively present in Homo sapiens. It has no protein-coding function and lacks a specific open reading frame (ORF) [5], which was considered to be a nonsignificant byproduct of transcription in the early stage [6][7][8]. Over the years, due to the advancement of highresolution chips and high-throughput sequencing technologies, the research on transcriptome regulation has been increasingly deepened, and it is found that lncRNA not only plays a significant role in transcriptional interference but also in the process of some histological development, tumorigenesis, and tumor metastasis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Liver cancer is a common malignant tumor, with a 15-17% 5-year survival rate (1,2). The prognosis of patients with liver cancer is poor due to the high frequency of postoperative recurrence and metastasis (3).…”
Section: Abstract Liver Cancer Linc01234 Usp4 Mir-513a-5pmentioning
confidence: 99%
“…Liver cancer is a common malignant tumor, with a 15-17% 5-year survival rate (1,2). The prognosis of patients with liver cancer is poor due to the high frequency of postoperative recurrence and metastasis (3).…”
Section: Introductionmentioning
confidence: 99%